Analisa Kualitas Air Budidaya Udang Vaname (Litopenaeus vannamei) di Tambak Rakyat Kontruksi Dinding Semen Dan Dasar Tambak Semen Di Pantai Konang, Kecamatan Panggul Kabupaten Trenggalek - Musyaffa Rafiqie (Samakia : Jurnal Ilmu Perikanan, 2021)
The water quality analysis activities carried out by smallholder farmers with the construction of cement walls and cement pond bases on the Konang beach, Panggul District, Trenggalek Regency, have not met the standard standards in the analysis of pond water quality. Pond farmers only analyze the pH, brightness and temperature of the pond water. The research objective was to obtain information and describe the analysis of water quality in the community pond construction of cement walls and the bottom of cement ponds at Konang beach, Panggul District, Trenggalek Regency. The activity of analyzing the water quality of the community plots of construction of cement walls and the bottom of the cement ponds on the Konang beach, Panggul District, Trenggalek Regency, was observed in the form of temperature, brightness and pH, with a pond area of ​​250 m2. Water quality observation activities for 30 days, in one day water quality observations are made twice, namely in the morning and evening. The pH measurement results were obtained, ranging from 7.4 to 8.5, so that the results of measuring the pH of the water in the people's ponds in Koneng Beach were still normal or normal. According to Boyd (2001) in Andi S and Sahabuddin (2014), it is said that water organisms (fish or shrimp) require a pH range of 6.8 - 8.5. the results of measuring the brightness with a simple tool, the measurement results are between 25-40 cm. Badrudin et al (2014) stated that the optimum brightness level of pond water which is influenced by plankton density is around 20 - 40 cm. So that the level of brightness can be concluded that it is still in rational or optimal. The temperature in the ponds was 24 ᴼC - 28 ᴼC, still within normal or optimal. According to Supito (2017), the pond temperature in the range of 28 ᴼ C to 32 ᴼ C is the optimal temperature forcultivating vaname shrimp.